2012
DOI: 10.1021/jf301218k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation Time and Vegetable Concentrate Addition on Quality Parameters of Organic Botifarra Catalana, a Cured–Cooked Sausage

Abstract: The effects of the addition of two different sources of nitrite (pure NaNO2 or a nitrate-rich vegetable concentrate) and three different fermentation times with nitrate-reducing cultures (6, 12, or 24 h at 16 °C) on microbial counts, pH, residual nitrate and nitrite amounts, and susceptibility to oxidation of botifarra catalana sausage were studied. Moreover, curing efficiency, color, tocopherol and tocotrienol contents, oxidative status, and consumer acceptability of these sausages were assessed after vacuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
16
2
Order By: Relevance
“…In the case of reformulated sausages, other factors have to be taken into account. In the given conditions, the colour that developed in RC and RA samples is attributable to the action of the added colouring in all cases, to the effect of the nitrifying agents (nitrate which is reduced to nitrite) in the celery (Chung et al 2004;Sindelar et al 2007a, b;Magrinya et al 2009Magrinya et al , 2012, and to a lesser extent to the ODF.…”
Section: Texturementioning
confidence: 87%
See 1 more Smart Citation
“…In the case of reformulated sausages, other factors have to be taken into account. In the given conditions, the colour that developed in RC and RA samples is attributable to the action of the added colouring in all cases, to the effect of the nitrifying agents (nitrate which is reduced to nitrite) in the celery (Chung et al 2004;Sindelar et al 2007a, b;Magrinya et al 2009Magrinya et al , 2012, and to a lesser extent to the ODF.…”
Section: Texturementioning
confidence: 87%
“…To limit this unhealthy effect, there have been proposals for the omission or lowering of nitrite/nitrate (by means of different alternatives for colour, lipid oxidation and safety purposes) in meat processing, and the application of strategies to inhibit damage due to nitros(yl)ation reactions (Pegg and Shahidi 2000;EFSA 2003;Zarringhalami et al 2009). The use of non-meat ingredients which by nature contain high nitrate levels, such as celery, has been proposed to avoid direct addition of nitrite to meat products (Sindelar et al 2007a, b;Magrinya et al 2009Magrinya et al , 2012Tahmouzi et al 2013). However, the modification and processing conditions needed to replace it may affect the technological properties and quality of meat products in different ways depending on the type of product.…”
Section: Introductionmentioning
confidence: 99%
“…Food Science and Technology International 0(0) previous results at nitrite source concentrations equivalent to 80 mg NaNO 2 /kg (Magrinya et al, 2012). Table 3 shows that VC affected the curing process, because those sausages in which this nitrite source was used seemed to have a lower curing efficiency.…”
Section: Total and Cured Pigment Analysesmentioning
confidence: 97%
“…The interactions found for the hue angle and chroma values are probably also a consequence of the intense nitrate reductase activity of the S. carnosus culture. In addition, several authors (Magrinya et al, 2012;Terns et al, 2011aTerns et al, , 2011bTsoukalas et al, 2011) have found that similar VC produced lighter and yellower sausages compared to those made with pure sodium nitrite, and this was also attributed to the intrinsic color of the powder. The color of the sausages was constant throughout storage.…”
Section: Color Measurementsmentioning
confidence: 99%
See 1 more Smart Citation